Severe Acute Respiratory Syndrome Coronaviruses with Mutations in the E Protein Are Attenuated and Promising Vaccine Candidates - Regla-Nava, Jose A. (J Virol, 2015)
Severe acute respiratory syndrome coronavirus (SARS-CoV) causes a respiratory disease with a mortality rate of 10%. A mouse-adapted SARS-CoV (SARS-CoV-MA15) lacking the envelope (E) protein (rSARS-CoV-MA15-ΔE) is attenuated in vivo. To identify E protein regions and host responses that contribute to rSARS-CoV-MA15-ΔE attenuation, several mutants (rSARS-CoV-MA15-E*) containing point mutations or deletions in the amino-terminal or the carboxy-terminal regions of the E protein were generated. Amino acid substitutions in the amino terminus, or deletion of regions in the internal carboxy-terminal region of E protein, led to virus attenuation. Attenuated viruses induced minimal lung injury, diminished limited neutrophil influx, and increased CD4(+) and CD8(+) T cell counts in the lungs of BALB/c mice, compared to mice infected with the wild-type virus. To analyze the host responses leading to rSARS-CoV-MA15-E* attenuation, differences in gene expression elicited by the native and mutant viruses in the lungs of infected mice were determined. Expression levels of a large number of proinflammatory cytokines associated with lung injury were reduced in the lungs of rSARS-CoV-MA15-E*-infected mice, whereas the levels of anti-inflammatory cytokines were increased, both at the mRNA and protein levels. These results suggested that the reduction in lung inflammation together with a more robust antiviral T cell response contributed to rSARS-CoV-MA15-E* attenuation. The attenuated viruses completely protected mice against challenge with the lethal parental virus, indicating that these viruses are promising vaccine candidates. IMPORTANCE Human coronaviruses are important zoonotic pathogens. SARS-CoV caused a worldwide epidemic infecting more than 8,000 people with a mortality of around 10%. Therefore, understanding the virulence mechanisms of this pathogen and developing efficacious vaccines are of high importance to prevent epidemics from this and other human coronaviruses. Previously, we demonstrated that a SARS-CoV lacking the E protein was attenuated in vivo. Here, we show that small deletions and modifications within the E protein led to virus attenuation, manifested by minimal lung injury, limited neutrophil influx to the lungs, reduced expression of proinflammatory cytokines, increased anti-inflammatory cytokine levels, and enhanced CD4(+) and CD8(+) T cell counts in vivo, suggesting that these phenomena contribute to virus attenuation. The attenuated mutants fully protected mice from challenge with virulent virus. These studies show that mutations in the E protein are not well tolerated and indicate that this protein is an excellent target for vaccine development.